Meningkatkan Rasa Percaya Diri Peserta Didik SMP dengan Menggunakan Teknik Assertive Training - Kamil, Badrul; Monica, Mega Aria; Maghrobi, A. Busthomi (Universitas Islam Negeri Raden Intan Lampung, 2018)
Self-confidence is the positive attitude of an individual that enables him to develop positive judgments both for himself and for his environment / situation. The purpose of this study was to determine whether group counseling services with assertive assistive techniques were effective in improving students' self-esteem. The method used in this research is True Experimental Design Design type pretest-posttest control group design. Data collection techniques in this study using observation, questionnaire method, interviews, and supporting technique documentation. The results of the data analysis show that there is an increase in the learner in the school before the service is given and after the service is provided. to confidence This is directed from the results of hypothesis testing by using t test (t-test), from the pretest and posttest results obtained in the experimental group t arithmetic = 36.701> t table 0.05 = 2.228, df = n-1 = 10 with p value <t table (0.000 <0.0005), then Ho